2004
DOI: 10.1107/s0108768104025947
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigations of phosphorus–nitrogen compounds. 6. Relationships between molecular parameters in per-X-substituted bridged spermine derivatives and basicity constants ΣαR of substituents

Abstract: A systematic study is reported of the products of the nucleophilic substitution reactions of the spermine-bridged cyclotriphosphazene, [N 3 t , respectively. A comparison has been made between the sum of the substituent basicity constants, AE R , obtained in nitrobenzene solution, and ten molecular parameters of the N 3 P 3 ring (the internal bond angles , , , and , and the PÐN bond lengths a, b, c, d and e) as well as the difference between the bond lengths a and b, Á(PÐN). It is found that the systematic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The structures of compounds 4 and 8 may be compared with previously reported single-bridged cyclotriphosphazene compounds, 19,23 in which a flexible alkyl bridge allowed rotation to form a range of conformations for the two cyclotriphosphazene rings in principle, but either syn or anti conformations were observed in practice. In the case of compounds 4 and 8, the rotation of the cyclotriphosphazene rings is restricted because of the rigid fluorenylidene bridges, and it is only provided by P-O-C or P-N-C moieties.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…The structures of compounds 4 and 8 may be compared with previously reported single-bridged cyclotriphosphazene compounds, 19,23 in which a flexible alkyl bridge allowed rotation to form a range of conformations for the two cyclotriphosphazene rings in principle, but either syn or anti conformations were observed in practice. In the case of compounds 4 and 8, the rotation of the cyclotriphosphazene rings is restricted because of the rigid fluorenylidene bridges, and it is only provided by P-O-C or P-N-C moieties.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…In addition there are a number of other bridged cyclophosphazenes that provide suitable spiro and/or ansa structures for comparison purposes; viz. the two mono-spiro-monoansa spirane derivatives (8a) and (8b), 6 a number of tri-spiranes (9) with non-geminal di-substituted cyclophosphazene rings, 5 spermine-bridged compounds with 1,3-propanedioxy rings in mono-spiro (10), 25 di-mono-spiro (11), 26 di-mono-ansa (12), 25 di-spiro-mono-ansa ( 13) 25 and tetra-spiro ( 14) 27 configurations.…”
Section: Comparison Of Spiro and Ansa Moieties In The Derivatives Of ...mentioning
confidence: 99%
“…The asymmetric unit of all compounds includes only one molecule and the cyclotriphosphazene rings are fully substituted with octamethyl-, ethyl-, propyl-, butyl-, and benzylparabens, as shown in ball−stick represantations in Figures 3 and 4 14)°, and are somewhat larger than those of the above-mentioned N−P− N angles. Analysis of previously reported crystallographic studies on spermine-bridged cyclophosphazene derivatives showed that a free rotation around single C−C bound in the flexible alkyl-chain could lead to the two conformations, which is identified as syn (CSD refcode: COPTUW01, 42 PAJVUS, 43 GUZPOG, 44 GUZPIA 44 or anti (CSD refcode: COPTUW, 41 BADJEW, 45 BADJIA, 45 CEGNEI, 46 CEGNIM, 46 GIFBAA 34 ) conformations of the cyclophosphazene moiety with respect to each other. In all compounds, two cyclotriphosphazenes stand in anti-conformation to each other, possibly under the influence of crowded paraben groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%